EPIPHYTIC LICHENS IN THE TOWN OF ZVEČAN AND THEIR BIOINDICATIOR S VALUE - Aleksić, Gordana; Stamenković, Slaviša; Ristić, Svetlana; Marković, Marija (Bulletin of Natural Sciences Research, 2019)
This paper treats the long-term changes in area of the "lichen desert" of town Zvečan. Comparison of results obtained in 1926, when 67 lichen species where present, through the results in 1983 and 1988 when the "lichen desert", low or no lichen diversity was established because of the air pollution, with investigations carried out in 2014, 16 lichen species were identified. The "lichen desert" is no existing any more. The main reason that the lichens are present now is termination of operation of the "Trepča" company and cessation primary pollutants emissions. Using lichens as a bio-indicators in this investigation it was established the average air pollution, which is lichen "struggle zone",meaning increase air quality.
Keywords: "Lichen desert"; Lichen "struggle zone"; Bio-indicators; Air quality; Zvečan